Comparison of Line Probe Assay (LPA) and Mycobacterium Growth Indicator Tubes (MGIT) Assay for Second-line TB Drug Susceptibility Testing - Towifah Fauziah Choerunisa; Leni Lismayanti; Tiene Rostini; Ryan Bayusantika; Ida Parwati (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Tuberculosis (TB) infection is one of the most prominent health issues in the world, including in Indonesia. TB is evolving into multidrug-resistant tuberculosis (MDR-TB) and requiring second-line TB drugs. Mycobacterium growth indicator tube (MGIT) is the gold standard for susceptibility testing of second-line TB drugs. Alternatively, line probe assay (LPA), which detects genes resistant to second-line TB drugs, takes a shorter time to run. This study aims to compare MGIT and LPA's ability to detect TB resistance to second-line TB drugs and observe mutation patterns of genes encoding second-line TB drugs.METHODS: This was an observational analytic study, using cross-sectional method. The data were acquired from the MDR-TB clinic’s medical records at the Dr. Hasan Sadikin Hospital from September to December 2019. LPA and MGIT test were conducted at the Health Laboratory Hall of West Java Province, then tested using Kolmogorov-Smirnov and chi-square statistic.RESULTS: From 121 subjects, 113 people were not resistant to the second-line TB drugs, which was examined using both LPA and MGIT (93.4%), p=0.991. Mutations were found in gyrA and rrs gene. There was no significant difference between the proportion of subjects resistant to the second-line of TB drugs tested using LPA and MGIT.CONCLUSION: LPA is an alternative method to MGIT because it requires a shorter time and reduces the risk of exposure that will improve MDR-TB patients management.KEYWORDS: line probe assay (LPA), multidrug-resistant TB, mycobacterium growth indicator tube (MGIT), second-line TB drugs